Profiling the variability and inequity in the residential environment in Cyprus according to citizens’ ratings: a cross-sectional internet-based “Place Standard” survey - Daphne Kleopa; Andrie Panayiotou; Christiana Kouta; Chrystalla Kaiafa; Nicos Middleton (BMC Public Health, 2022)
Abstract Background The “Place Standard Tool” (PST) offers a practical framework for structuring conversations about physical and social dimensions of Place which impact on health and well-being. The aim of this study was to survey citizens’ perceptions of Place across diverse settings in Cyprus. While the PST has been extensively used in the context of community engagement, its properties as a measurement tool haven’t been explored. Methods An open call was addressed to citizens to rate their neighbourhood environment across the 14 PST items (1: large to 7: little room for improvement). Exploratory factor, cluster and regression analyses were used to explore the dimensionality of the scale, depict neighbourhood profiles and explore differences in ratings according to socio-demographic characteristics, area-level census indicators and residents’ assessment of neighbourhood social position (10-step ladder). Results With the exception of safety (M = 4.4, SD = 1.7), 492 participants (mean age 42, 50% residents for > 10 years) from 254 postcodes (21.7% islandwide) did not rate other features favourably, with lowest scores for “influence and sense of control” and “public transport”. A stepwise pattern of dissatisfaction was observed along the social position continuum both for features rated less as well as more favourably (e.g. social contact). For instance, among participants who placed their neighbourhood at the three top steps of the ladder, 48.8% gave a low rating for “influence and sense of control”, while the equivalent figure was 81.0% at the bottom three steps (OR = 4.5, 95% CI 2.3, 8.6). A clear dimensionality of Built (6 items, Cronbach’s α = 0.798), Physical (3 items, α = 0.765), Social (2 items, α = 0.749) and Service (3 items, α = 0.58) environment was identified. A social gradient was evident according to census measures of socio-economic disadvantage (e.g. pre-1980 housing, single-parent households) with larger differences in terms of the built than the social environment. Conclusions The study profiled the variability and documented the inequity in the health-related neighbourhood environment across Cypriot communities. The readily interpretable dimensionality of the scale supports its construct validity, allowing calculation of composite scores. The PST can be used as measurement tool in research as well as public health practice to advocate for neighbourhood initiatives which support and enhance citizens’ participation.